2022
DOI: 10.1002/mp.15419
|View full text |Cite
|
Sign up to set email alerts
|

Automatic coronavirus disease 2019 diagnosis based on chest radiography and deep learning – Success story or dataset bias?

Abstract: Purpose: Over the last 2 years, the artificial intelligence (AI) community has presented several automatic screening tools for coronavirus disease 2019 based on chest radiography (CXR), with reported accuracies often well over 90%. However, it has been noted that many of these studies have likely suffered from dataset bias, leading to overly optimistic results. The purpose of this study was to thoroughly investigate to what extent biases have influenced the performance of a range of previously proposed and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Also, the comparison is limited by the number of deep learning models employed, i.e., only three in this study. Recent studies showed that a dataset, when collected from different sources, can lead to dataset bias [51,52] where the model learns the source of the images rather than the disease itself. Images from different sources can have different characteristics, such as overall pixel intensities and corner labels, and may present electrodes with cables in the X-ray, bras, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the comparison is limited by the number of deep learning models employed, i.e., only three in this study. Recent studies showed that a dataset, when collected from different sources, can lead to dataset bias [51,52] where the model learns the source of the images rather than the disease itself. Images from different sources can have different characteristics, such as overall pixel intensities and corner labels, and may present electrodes with cables in the X-ray, bras, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches may lead to high variance estimation of deep learning models’ performance during the test phase [131] . Since many of the COVID-19 prediction models are poorly reported, and at high risk of bias and model overfitting [132] , more investigation will be needed to ensure the performance of these models in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Even, sensitivity values of 100% in automatic classification are reported [13,14]. However, other studies demonstrate the lack of generalization of the models, by notably lowering the performance index when trying to classify images that do not come from the same distribution (ood) with which they were trained [15][16][17][18][19][20][21]. In other words, these proposed models suffer from the inherent drawbacks of low generalization capability, derived from the sparse labeled COVID-19 data [22].…”
Section: Cxr Imaging As a Diagnostic Methodsmentioning
confidence: 99%